Male sex hormone as a correlate of endothelial function in middle-aged Indian males: a cross-sectional prospective observational study - Mohan, Chandra; Gururani, Kunal; Rawat, Anurag; Kala, Mansi (International Journal of Research in Medical Sciences, 2021)
Background: Data on relationship between serum testosterone and endothelial dysfunction measured by brachial artery flow-mediated dilatation (BAFMD) in Indian subset are scarce. The present study was envisaged to assess the correlation between serum testosterone and endothelial dysfunction measured by BAFMD. Methods: From October 2013 till September 2014, 92 Indian male patients aged 40-60 years who underwent investigation of flow-mediated dilatation of the brachial artery using ultra sonography were included. The association between serum testosterone and BAFMD percent-measured endothelial dysfunction was examined. Results: Multivariate regression analysis in 92 Indian male patients (mean age 53.12±6.3 years) revealed that low levels of total serum, serum free and serum bioavailable testosterone were significantly associated with BAFMD% and were independent of age, hypertension, diabetes, body mass index (BMI), current smoking and hyperlipidaemia (p<0.001). The total serum, serum free and serum bioavailable testosterone were positively correlated with BAFMD% with Pearson correlation coefficients of r=0.572, r=0.525 and r=0.547, respectively (p<0.001). Conclusions: Low levels of total serum, serum free and serum bioavailable testosterone were significantly associated with BAFMD%-measured endothelial dysfunction, irrespective of cardiovascular risk factors.